Using Computer Assisted Language Learning (CALL) in Post-Pandemic Era: Higher Education Students’ Voice (Conference on English Language Teaching, 2023)
Covid-19 which occurred at the end of 2019 resulted in many changes occurring in the community, including in the world of education, especially in higher education. Computer Assisted Language Learning (CALL) is the use of computers as language learning aids in education which requires the teaching and learning process to utilize technology. The purpose of this study is to find out how English students in higher education perceive the use of Computer Assisted Language Learning (CALL) after the covid-19 pandemic. The method used in this research is descriptive qualitative. Collecting data in this study using a questionnaire with opened and closed-ended questionnaire with twenty students of Higher Education. The results of this study indicated that the use of Computer Assisted Language Learning (CALL) that helped English students in Higher Education to learned languages even though the covid-19 pandemic has ended. It can be concluded that most students in Higher Education have a positive perception of the use of CALL for language learning after the pandemic era.